Building an Altar Despite Animosity A Literary Defense of the Concessive Reading of Ezra 3:3a - Byun, Paul (2020)
A common scholarly understanding is that the first group of returnees in Ezra 3:3a built an altar "because they were in dread of the neighboring peoples." I find such a reading to be unlikely for three reasons. First, a study of Ezra 3:3a reveals that accepting the common understanding generates an awkward reading. Second, the returnees are never characterized as a group building in response to external threats. Third, the motive behind altar building elsewhere in the Hebrew Bible is strictly for sacrifices. I suggest that a more compelling reading of Ezra 3:3a is, "They set up the altar on its foundation, although they were in dread of the neighboring peoples."
Keywords: Altars in the Bible; Bible. Ezra; Bible. Nehemiah; BIBLE. Old Testament; Criticism, interpretation, etc; BIBLE; History of Biblical events; Ezra-Nehemiah; altar building; returnees